Lack of Elevated Expression of TGFβ3 Contributes to the Delay of Epithelial Wound Healing in Diabetic Corneas - Gao, Nan; Yu, Fu-Shin (Investigative ophthalmology & visual science, 2024)
To investigate the mechanisms underlying the differential roles of TGFβ1 and TGFβ3 in accelerating corneal epithelial wound healing (CEWH) in diabetic (DM) corneas, with normoglycemia (NL) corneas as the control. Two types of diabetic mice, human corneal organ cultures, mouse corneal epithelial progenitor cell lines, and bone marrow-derived macrophages (BMDMs) were employed to assess the effects of TGFβ1 and TGFβ3 on CEWH, utilizing quantitative PCR, western blotting, ELISA, and whole-mount confocal microscopy. Epithelial debridement led to an increased expression of TGFβ1 and TGFβ3 in cultured human NL corneas, but only TGFβ1 in DM corneas. TGFβ1 and TGFβ3 inhibition was significantly impeded, but exogenous TGFβ1 and, more potently, TGFβ3 promoted CEWH in cultured TKE2 cells and in NL and DM C57BL6 mouse corneas. Wounding induced similar levels of p-SMAD2/SMAD3 in NL and DM corneas but weaker ERK1/2, Akt, and EGFR phosphorylation in DM corneas compared to NL corneas. Whereas TGFβ1 augmented SMAD2/SMAD3 phosphorylation, TGFβ3 preferentially activated ERK, PI3K, and EGFR in healing DM corneas. Furthermore, TGFβ1 and TGFβ3 differentially regulated the expression of S100a9, PAI-1, uPA/tPA, and CCL3 in healing NL and DM corneas. Finally, TGFβ1 induced the expression of M1 macrophage markers iNOS, CD86, and CTGF, whereas TGFβ3 promoted the expression of M2 markers CD206 and NGF in BMDMs from db/db or db/+ mice. Hyperglycemia disrupts the balanced expression of TGFβ3/TGFβ1, resulting in delayed CEWH, including impaired sensory nerve regeneration in the cornea. Supplementing TGFβ3 in DM wounds may hold therapeutic potential for accelerating delayed wound healing in diabetic patients.